Diversity, endemism, and geographical distribution of scaly tree ferns in Asia - Rajapaksha, Ranil; Pham, van The; Chamara, Ruwan; Wardani, Wita; Coritico, Fulgent P.; Mustapeng, Andi Maryani A.; Suleiman, Monica; Ojha, Rijan; Cicuzza, Daniele; Ebihara, Atsushi; Islam, Taherul; Huang, Yao-Moan; et al. (Phytotaxa, 2025)
South and Southeast Asia are considered important centers of diversity for scaly tree ferns (Cyatheaceae). Following an extensive review of existing checklists from each Asian country, combined with the expert knowledge of the authors, a comprehensive checklist was compiled. The checklist comprises 185 species belonging to four genera: Alsophila (92 spp.), Cyathea (1 sp.), Gymnosphaera (27 spp.), and Sphaeropteris (65 spp.). Indonesia harbors the highest number of species (117), followed by Malaysia (including Malaysian Borneo) and the Philippines, each with 39 species, highlighting Indonesia’s exceptional contribution to the region’s species diversity. Indonesia also exhibits the highest level of endemism, with 48 endemic species (26%), while the Philippines and Malaysia have 25 and 12 endemic species, respectively. When considering the proportion of endemic species relative to the total number of species recorded in each country, Sri Lanka ranks first, with 71% endemism. The genus Alsophila significantly contributes to endemism in India, Indonesia, Malaysia, the Philippines, and Sri Lanka. The genus Alsophila accounts for 100% of the endemic species in Sri Lanka, while the genus Gymnosphaera accounts for 100% of the endemic species in Vietnam. We hope that this checklist will provide a useful foundation for future studies in taxonomy, biogeography, and conservation, and will contribute to informed management and protection of these species in their natural environments.